Does intellectual capital efficiency affect financial performance? The case of Italian listed firms. (1st January 2014) - Guerrini, Andrea; Romano, Giulia; Leardini, Chiara
This article answers two key research questions, namely, if and how a firm's IC efficiency directly affects current and future financial performance. The analysis includes 218 publicly listed Italian companies and their annual reports from 2008 to 2010. In line with previous studies, the authors measure IC capital using an existing model, which relies on a value-added intellectual coefficient (VAIC) and thus can quantify IC with data from firms' annual reports. The economic performance of Italian listed companies is strictly linked to the presence of intangible and invisible resources, which contribute to create wealth. This article offers the first inquiry into the relationship between IC and profit for Italian listed companies, using the VAIC. Italy provides a potentially interesting environment for investigating this issue, because Italian products are widely and globally appreciated for their intangible features (e.g., design, brands, and taste).